2003
DOI: 10.1074/jbc.m210419200
|View full text |Cite
|
Sign up to set email alerts
|

Familial Amyotrophic Lateral Sclerosis Mutants of Copper/Zinc Superoxide Dismutase Are Susceptible to Disulfide Reduction

Abstract: We observed that 14 biologically metallated mutants of copper/zinc superoxide dismutase (SOD1) associated with familial amyotrophic lateral sclerosis all exhibited aberrantly accelerated mobility during partially denaturing PAGE and increased sensitivity to proteolytic digestion compared with wild type SOD1. Decreased metal binding site occupancy and exposure to the disulfide-reducing agents dithiothreitol, Tris(2-carboxyethyl)phosphine (TCEP), or reduced glutathione increased the fraction of anomalously migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
193
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(216 citation statements)
references
References 66 publications
19
193
2
2
Order By: Relevance
“…Metal-free forms of SOD1 have been proposed to be the toxic precursor preceding aggregation in familial aLS [43,44]. the majority of aLS mutations affect the structural stability of SOD1, leading to the exposure of buried hydrophobic residues, thus resulting in aggregation [45]. hence SOD1 Wt has an intrinsic propensity to aggregate which is enhanced by mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Metal-free forms of SOD1 have been proposed to be the toxic precursor preceding aggregation in familial aLS [43,44]. the majority of aLS mutations affect the structural stability of SOD1, leading to the exposure of buried hydrophobic residues, thus resulting in aggregation [45]. hence SOD1 Wt has an intrinsic propensity to aggregate which is enhanced by mutation.…”
Section: Discussionmentioning
confidence: 99%
“…9). Several papers (41,46) have also reported that H46R is less stable than other FALS mutants in vitro. Most interestingly, the immunoreactivities of H46R against the mAbs in Western blot and ELISA were similar to that of WT or C111S (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…9C). Tiwari and Hayword (41) reported that, in the presence of disulfide-reducing agents, FALS mutant SODs were more susceptible than WT to aberrant migration during partially denaturing SDS-PAGE and to proteolytic digestion. A conserved internal disulfide bond between Cys-57 and Cys-146 also contributes to the stability of Cu/Zn-SOD.…”
Section: Discussionmentioning
confidence: 99%
“…These SOD1 multimers could be involved in protein aggregation and the pathology of amyotrophic lateral sclerosis. Interestingly, increased susceptibility to disulfide reduction has been observed in some fALS mutants (36); therefore, protein monomerization caused by the disulfide reduction and demetallation might be an important process in causing the fALS diseases.…”
Section: Discussionmentioning
confidence: 99%